MOSCOW CITY SCIENTIFIC-PRACTICAL CONFERENCE “DIAGNOSTIC AND TREATMENT STRATEGY IN COMBINED TRAUMA OF THE CHEST ABDOMEN” - M. M. Abakumov (Неотложная медицинская помощь)
Moscow city scientific-practical conference “Diagnostic and treatment strategy in combined trauma of the chest abdomen”.